Challenges of Managing Lower Urinary Tract Symptoms in Women with Tamoxifen Use - Ethan M. Fan; Philippe E. Zimmern (Mary Ann Liebert, 2022)
Objective: Tamoxifen complicates management of conditions such as urinary tract infections (UTIs), urinary incontinence (UI), and/or pelvic organ prolapse (POP) that traditionally benefit from hormonal intake; thus, we reviewed our experience in managing these hormonally deprived women. Materials and Methods: After IRB approval, electronic medical records from women with current use or history of tamoxifen use and referred to a tertiary care center with female pelvic medicine and reconstructive surgery expertise for UTI, UI, and/or POP were reviewed. Results: From 2015 to 2020, 32 women treated with tamoxifen 10?40?mg for a median of 4 years were referred for UTIs (9), UI (10), symptomatic POP (8), or for a combination of these (5). Participants with UTI treated with antibiotics, prophylactic supplements, and/or electrofulguration had satisfactory response at median follow-up of 1 year (interquartile range [IQR]: 0.5?1). Ten of 15 women with UI chose intervention, with no self-reported UI recurrence at median follow-up of 2.5 years (IQR: 1?3). All but one participant with POP underwent vaginal or open/robotic mesh repairs, with satisfactory outcomes at median follow-up of 3 years (IQR: 2?7). Conclusions: The management of UTIs, UI, and POP in women on tamoxifen or unable to benefit from hormonal intake is challenging, but traditional interventions can be considered with satisfactory results.